Prostaglandin Endoperoxides and Thromboxane A2 Activate the same Receptor Isoforms in Human Platelets - Vezza, Roberta; Mezzasoma, Anna Maria; Venditti, Gigliola; Gresele, Paolo (Thrombosis and Haemostasis, 2002)
Arachidonic acid (AA) is a potent inducer of platelet aggregation in vitro; this activity is due to its conversion to biologically active metabolites, prostaglandin (PG) endoperoxides and thromboxane A2 (TxA2). PG endoperoxides and TxA2 are thought to act on the same receptor; however, at least two isoforms of this receptor have been identified. The aim of our work was to clarify whether endoperoxides and TxA2 activate the same or different receptor subtypes to induce aggregation and calcium movements in human platelets.AA-induced aggregation and calcium rises were still detectable in platelets preincubated with thromboxane synthase inhibitors, which suppress TxA2 formation and induce PGH2 accumulation, suggesting that PG endoperoxides can activate platelets. Exogenously added PGH2 was able to induce aggregation and calcium rises. Pretreatment of platelets with GR32191B or platelet activating factor, which desensitize one of the two receptor subtypes identified in platelets, did not prevent calcium rises induced by endogenously generated or by exogenouly added PGH2, indicating that TxA2 and PG endoperoxides share the same receptor subtype(s) to activate platelets. HEK-293 cells overexpressing either of the two thromboxane receptor isoforms cloned to date (TPα and TPβ) and identified in human platelets, stimulated with PGH2, or with the stable endoperoxide analog U46619, formed inositol phosphates. These data show that endoperoxides and TXA2 mediate their effects on platelets acting on both, and the same, receptor isoform(s).Abbreviations: AA: arachidonic acid; PAF: platelet activating factor; PG: prostaglandin; TP: thromboxane receptor; Tx: thromboxane.
Keywords: Platelet aggregation; calcium; thromboxane receptor isoforms